Job Insecurity, Engagement, and Mental Health: Drivers of Turnover Intentions at PT. Pos Indonesia: Ketidakpastian Pekerjaan, Keterlibatan, dan Kesehatan Mental: Faktor Pendorong Niat Pindah Pekerjaan di PT. Pos Indonesia - Wahyu Maulana; Nuzulul Qurnain; Istianah Asas (Universitas Muhammadiyah Sidoarjo, 2025)
This study examines the effects of job insecurity and employee engagement on turnover intention, with mental health as a mediating variable, among employees at PT. Pos Indonesia. Using an associative quantitative approach and a saturated sample of 101 respondents, data were analyzed through Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that job insecurity does not significantly affect mental health or turnover intention. In contrast, employee engagement has a positive and significant impact on both mental health and turnover intention. However, mental health did not mediate the relationships between job insecurity or employee engagement and turnover intention. Notably, high levels of engagement appear to increase turnover intention, likely due to work-related pressure and unbalanced workloads. These findings suggest that while engagement is beneficial, it may also lead to negative outcomes if not managed properly. The study implies that organizations should focus on equitable workload distribution, implement mental health support programs, and monitor work-related stress to better retain high-performing employees.